A Comparative Clinical Study of Lateral Lumbar Interbody Fusion between Patients with Multiply Operated Back and Patients with First-Time Surgery - Masato Nakano; Hayato Futakawa; Shigeharu Nogami; Miho Kondo; Tatsuro Imai; Yoshiharu Kawaguchi (Medicina, 2023)
Background and Objectives: Patients with multiply operated back (MOB) may suffer from persistent lower-back pain associated with back muscle damage and epidural fibrosis following repeated back surgery (Failed Back Spinal Syndrome). Lateral lumbar interbody fusion (LLIF) is considered to be favorable for MOB patients. However, little scientific research has been carried out for this issue due to variety of the pathogenesis. The purpose of this study was to compare the clinical results of MOB patients and first-time surgery patients who underwent LLIF for lumbar spinal stenosis with degenerative scoliosis and/or degenerative spondylolisthesis (spinal instability). Materials and Methods: LLIF was performed for lumbar spinal stenosis with spinal instability in 55 consecutive cases of single hospital (30 males, 25 females, average age: 69). Clinical outcomes were compared between the MOB patient group (MOB group) and the first surgical patient group (F group). We evaluated the Japanese Orthopaedic Association (JOA) scores and JOA Back Pain Evaluation Questionnaire (JOABPEQ) before and 2 years after surgery. MOB patients were defined as those who have had one or more lumbar surgery on the same intervertebral or adjacent vertebrae in the past. Results: There were 20 cases (12 males, 8 females, average age: 71) in MOB group, and 35 cases (19 males, 16 females, average age: 68) in the F group. There was no significant difference between the two groups in terms of age, sex, number of intervertebral fixations, modic change in fused intervertebral end plate, score of brief scale for evaluation of psychiatric problem, lumbar lordosis, and sagittal vertical axis before and after surgery. The preoperative JOA scores averaged 12.5 points in the MOB group and averaged 11.6 points in the F group. The postoperative JOA scores averaged 23.9 points in the MOB group and averaged 24.7 points in the F group. The preoperative JOABPEQ averaged 36.3 points in the MOB group and averaged 35.4 points in the F group. The postoperative average JOA score was 75.4 in the MOB group and 70.2 in the F group. Conclusions: Based on the results, there was no significant difference in clinical outcomes of the two groups, and there was no new residual lower-back pain. Thus, we considered that LLIF one option for patients with MOB.